S100A9 induces nucleus pulposus cell degeneration through activation of the NF‐κB signaling pathway. Issue 10 (18th March 2021) - Guo, Song; Su, Qihang; Wen, Junxiang; Zhu, Kai; Tan, Jun; Fu, Qiang; Sun, Guixin
Abstract: Oxidative stress in the lumbar disc leads to the degeneration of nucleus pulposus (NP). However, the molecular mechanisms underlying this process remain unclear. In this study, we delineated a key calcium‐binding protein, S100A9, which was induced by oxidative stress and was highly expressed in the degenerative NP. Immunofluorescence staining and Western blotting revealed that S100A9 induced NP cell apoptosis in vitro by up‐regulating the expression of pro‐apoptotic markers, including cleaved caspase‐3, cytochrome c and Bax. Moreover, RT‐PCR analyses revealed that the expression of S100A9 caused NP matrix degradation by up‐regulating the expression of matrix degradation enzymes and increased the inflammatory response by up‐regulating cytokine expression. Therefore, S100A9 induced NP cell degeneration by exerting pro‐apoptotic, pro‐degradation and pro‐inflammatory effects. The detailed mechanism underlying S100A9‐induced NP degeneration was explored by administering SC75741, a specific NF‐κB inhibitor in vitro. We concluded that S100A9 induced NP cell apoptosis, caused matrix degradation and amplified the inflammatory response through the activation of the NF‐κB signalling pathway. Inhibition of these pro‐apoptotic, pro‐degradation and pro‐inflammatory effects induced by S100A9 in NP may be a favourable therapeutic strategy to slow lumbar disc degeneration.